Perbaikan Dokumen ISO 9001:2015 Klinik Pratama Universitas Kristen Petra Mendukung Pencapaian Sasaran Mutu CSI - Raymond Andika Kopaloma; I Nyoman Sutapa (Jurnal Titra, 2021)
This study is about improving the quality document of Klinik Pratama at Univeristas Kristen Petra (UKP). The UKP Klinik Pratama sets several quality objectives, one of which is Customer Satisfaction Index (CSI) or patient satisfaction level which is not explicit enough or clearly stated in some of quality documents, such as Business Process, Standard Operating Procedure (SOP), and Work Instruction IK , so that in its implementation the quality objectives are not achieved optimally.double- The method used in this research is qualitative by relying on data and information from relevant and competent sources. This study used secondary data, namely the quality documents belonging to the UKP Klink Pratama, ISO 9001: 2015 standards and primary data, namely the results of interviews with doctors and paramedics at the UKP Klink Pratama. Processing and discussion are carried out by aligning quality objectives and quality documents, so that the target of quality objectives is clearer and more focused. The results of this study is a the design to improve Business Process documents, especially the flow of patient treatment, improving the SOP, especially the flow of treatment for patients in dentistry and general clinic, also improvement of IK especially for dentistry.